Bound by Love : Familial Bonding in Film and Television since 1950. - D'Amore, Laura Mattoon (Cambridge Scholars Publishing, 2011)
What does it mean to be bound by love? In some cases bonds imprison and restrict, forcing captives to fight for survival. In others they promise unconditional love and acceptance, an eternal link from one soul to another. By tracing the historical lessons that have been taught in film and television about love, marriage, and parenthood, Bound by Love compellingly demonstrates a popular cultural dialogue about the changing nature of the American family over the past sixty years. The essays ...